Doubly Doped BaZnOS Microcrystals for Multicolor Luminescence Switching. Issue 7 (27th January 2022) - Wang, Yanze; Chen, Bing; Zhang, Xin; Suo, Hao; Zheng, Weilin; Shen, Junda; Li, Yang Yang; Wang, Feng
Abstract: Quaternary oxysulfide semiconductors with a formula of MZnOS (M = Ca, Sr, or Ba) have recently attracted a lot of attention as host materials for luminescent dopant ions. Among these oxysulfides, the BaZnOS remains largely unexplored for luminescence in comparison with the CaZnOS and SrZnOS counterparts. This study describes a highly efficient and repeatable synthesis of BaZnOS microcrystals comprising a variety of lanthanide and transition metal ions. Spectroscopic investigations reveal a host‐sensitized luminescence in the dopant ions that display distinct temperature dependence of emission intensity. Accordingly, a class of BaZnOS crystals doubly doped with Pr 3+ and Mn 2+ is further constructed, which shows a sensitive switching of luminescence color in response to temperature change. The advances in these luminescent nanomaterials offer exciting opportunities for temperature sensing (relative sensitivity of 8.58% K –1 ) and electrochromism applications. Abstract : Pr 3+ and Mn 2+ doubly doped BaZnOS crystals are synthesized and explored for multicolor luminescence switching. The Pr 3+ and Mn 2+ dopants display different temperature‐dependent emissions, rendering yellow to red color tuning under the heating of a thermoelectric device. By correlating the emission intensity ratio of Pr 3+ and Mn 2+ ions with temperature, a ratiometric luminescence thermometer is demonstrated with a high relative sensitivity of 8.58% K –1 .